2007
DOI: 10.1186/1742-4690-4-89
|View full text |Cite
|
Sign up to set email alerts
|

Asn 362 in gp120 contributes to enhanced fusogenicity by CCR5-restricted HIV-1 envelope glycoprotein variants from patients with AIDS

Abstract: Background: CCR5-restricted (R5) human immunodeficiency virus type 1 (HIV-1) variants cause CD4+ T-cell loss in the majority of individuals who progress to AIDS, but mechanisms underlying the pathogenicity of R5 strains are poorly understood. To better understand envelope glycoprotein (Env) determinants contributing to pathogenicity of R5 viruses, we characterized 37 full-length R5 Envs from cross-sectional and longitudinal R5 viruses isolated from blood of patients with asymptomatic infection or AIDS, referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
138
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(144 citation statements)
references
References 95 publications
4
138
2
Order By: Relevance
“…6 and 7, may be used to correlate the efficiency of CD4 and CCR5 usage with various aspects of viral pathogenicity. For example, the increased pathogenicity and/or fusogenicity of AIDS versus pre-AIDS R5 strains has been attributed to their increased efficiency of CD4 and/or CCR5 usage, as demonstrated by increased resistance to various entry inhibitors (31,44). Conversely, acutely transmitted "founder" viruses, though R5 tropic, can grow in activated PBMCs but not primary macrophages (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 and 7, may be used to correlate the efficiency of CD4 and CCR5 usage with various aspects of viral pathogenicity. For example, the increased pathogenicity and/or fusogenicity of AIDS versus pre-AIDS R5 strains has been attributed to their increased efficiency of CD4 and/or CCR5 usage, as demonstrated by increased resistance to various entry inhibitors (31,44). Conversely, acutely transmitted "founder" viruses, though R5 tropic, can grow in activated PBMCs but not primary macrophages (42).…”
Section: Discussionmentioning
confidence: 99%
“…For clade B infections, up to half of patients develop CXCR4 (X4)-tropic HIV type 1 (HIV-1) variants prior to or during the onset of clinical AIDS (28,30,51); however, X4 tropism can be rare in other clades (e.g., clades A and C) that predominate in countries where patients still clearly progress to AIDS (3,12). For patients with R5 viruses, HIV progression has been associated with enhanced macrophage tropism (1a, 22, 46), the increased ability to use low levels of CCR5 (11,44), and an increasing replicative fitness (45) and relative entry efficiency of the infecting virus (26,39). Neurovirulence is also correlated with an isolate's ability to use low levels of CD4 and/or CCR5 present on microglial cells (8,10,27).…”
mentioning
confidence: 99%
“…Previous studies demonstrated that alterations in gp120-CD4 interactions can impact viral infectivity and membrane fusion (8,22,31,32). To investigate whether reductions in ibalizumab susceptibility affect these Env-mediated functions, we assessed the in vitro infectivities of paired day 0 and week 9 virus isolates by comparing reporter gene expression levels in the HIV-1 entry assay.…”
Section: Vol 85 2011 Ibalizumab Susceptibility Of Hiv-1 3873mentioning
confidence: 99%
“…Both the V1/V2 length and the number of potential N-linked glycosylation sites (PNGSs) within gp120 have been reported to affect sensitivity to sCD4, CD4 binding site exposure, and/or fusogenicity (14,23,31). A comparison of the lengths and numbers of PNGSs for each of the variable regions of day 0 and corresponding week 9 clones is presented in Table 2.…”
Section: Vol 85 2011 Ibalizumab Susceptibility Of Hiv-1 3873mentioning
confidence: 99%
“…Although it is widely observed that M-tropic viruses are able to enter more efficiently at low CD4 densities (14,19,(22)(23)(24)(25)(26) and are more sensitive to neutralization by soluble CD4 (sCD4) (27)(28)(29) than T-tropic viruses, few other characteristics are widely agreed upon. Similarly, several amino acid changes in the HIV-1 Env protein have been associated with macrophage tropism (24,25,27,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), but the changes are not consistent across different subjects when macrophage tropism is defined as a distinct set of evolutionary variants within that subject (40). Furthermore, viruses isolated from the brain are sometimes referred to as neurotropic but without a clear definition of what this means phenotypically other than being located in the central nervous system (CNS) at the time of isolation.…”
mentioning
confidence: 99%